BS EN IEC 62442-2. Energy performance of lamp controlgear. Part 2. Controlgear for high intensity discharge lamps (excluding fluorescent lamps). Method of measurement to determine the efficiency of controlgear (16th October 2020) - British Standards Institution
No abstract available